Os cursos de licenciatura e a formação do professor: a contribuição da Universidade Federal de Uberlândia na construção do perfil de profissionais da educação - Mendes, Olenir Maria (1999)
This study had as its objective the analysis of fourteen degree course curriculum proposals from the Federal University of Uberlândia, seeking to know the configuration moviment of each course through the years and its relations with educational politics, inserted in the socio economical and political Brazilian context. The intention was to analyse the general and specific objectives of each of the proposals, relate the teacher s profile found in the main demands and necessities imposed by the in relation to the teacher s formation in Brazil and understand the condition for implementation of the proposals by analysing the curriculum of the courses studied. we adapted as a methodological category the study of the object inserted in a dynamic relationship with the context in which it is part. In this perspective, we intended to explain how the connections are stablished between historical determinants and the creation of degree courses at UFU and at other brazilian universities. For this purpose we examined the main documents refering to the criation and development of each course analysed, we interviewed courses coordenators to add informations to the study. The results shwed that the curriculum plans of the courses did not have the proposals and what was proposed more recently for degree in the country. what prevails is a certain valorization of specific knowledge to the detriment of pedagogical knowledge. The curriculum struture established for these courses presents a model that s criticizes and does not respond to the basic necessities of the social reality in respect to the teacher s formation. However new perspectives are apearing as an affort to overcome the problems that were shown in some of the proposals analysed.